Characterization of microvoids in thin hydrogenated amorphous silicon layers by spectroscopic ellipsometry and Fourier transform infrared spectroscopy. (October 2015) - Liu, Wenzhu; Zhang, Liping; Meng, Fanying; Guo, Wanwu; Bao, Jian; Liu, Jinning; Wang, Dongliang; Liu, Zhengxin
Graphical abstract: Abstract : Microstructures of voids in a-Si:H layers on the surface of c-Si wafers were quantitatively analyzed by combining spectroscopic ellipsometry and Fourier transform infrared spectroscopy. A diameter ( D ) from 0.52 to 2.11 nm and a number density ( N voids ) from 8.4 × 10 18 to 5.4 × 10 20  cm −3 were estimated. It was demonstrated large-size voids were formed owing to the network relaxation caused by H + etching. Measurements of the minority carrier lifetime revealed both D and N voids affect the passivation performance for a c-Si surface.